Response to Vapors of Volatile Organic Compounds of SnO2 Thin Film - (:unkn) unknown (AMER INST PHYSICS, 2009)
This work presents effect of the vapors of Volatile Organic Compounds (VOCs) on sol-gel derived undoped SnO2 thin film SnCl4 5H(2)O was dissolved in ethanol. After the solution is stirred for two hours 3 ml glacial acetic acid were added into the solution After the clear solution is obtained thin film of SnO2 was deposited by dipping method on glass substrate patterned with Interdigital Transducer (IDT). Final curing temperature was 573 K Crystal structure of the film was investigated using X-ray diffraction. Gas sensing properties of the film were determined by means of change in conductivity as a function of temperature and gas concentration. The film was tested for the vapors of ammonia, toluene, ethanol and water The film was also tested for the CO. Gas concentrations were controlled by MKS mass flow controller. The film was tested between the gas concentrations of 0 25% and 18%. All measurements were performed between the temperatures of 293 K - 573 K The film showed good sensitivity to VOCs vapors even at room temperature. The results showed that response parameters such as response time, recovery time depends on temperature and gas concentration
Keywords: Tin dioxide; sol-gel; sensor; VOC; thin film